Peak oxygen uptake cut‐points to identify children at increased cardiometabolic risk – The PANIC Study. (9th October 2018) - Agbaje, Andrew O.; Haapala, Eero A.; Lintu, Niina; Viitasalo, Anna; Barker, Alan R.; Takken, Tim; Tompuri, Tuomo; Lindi, Virpi; Lakka, Timo A.
Abstract : We aimed to develop cut‐points for directly measured peak oxygen uptake ( V ˙ O 2 peak ) to identify boys and girls at increased cardiometabolic risk using different scaling methods to control for body size and composition. Altogether 352 children (186 boys, 166 girls) aged 9‐11 years were included in the analyses. We measured V̇O2peak directly during a maximal cycle ergometer exercise test and lean body mass (LM) by bioelectrical impedance. We computed a sex‐ and age‐specific cardiometabolic risk score (CRS) by summing important cardiometabolic risk factors and defined increased cardiometabolic risk as >1 standard deviation above the mean of CRS. Receiver operating characteristics curves were used to detect V̇O2peak cut‐points for increased cardiometabolic risk. Boys with V̇O2peak <45.8 mL kg body mass (BM) −1  min −1 (95% confidence interval [CI] = 45.1 to 54.6, area under the curve [AUC] = 0.86, P  < 0.001) and <63.2 mL kg LM −1  min −1 (95% CI =52.4 to 67.5, AUC = 0.65, P  = 0.006) had an increased CRS. Girls with V̇O2peak <44.1 mL kg BM −1  min −1 (95% CI = 44.0 to 58.6, AUC = 0.67, P  = 0.013) had an increased CRS. V̇O2peak scaled by BM −0.49 and LM −0.77 derived from log‐linear allometric modeling poorly predicted increased cardiometabolic risk in boys and girls. In conclusion, directly measured V ˙ O 2 peak <45.8 mL kg BM −1  min −1 among boys and <44.1 mL kg BM −1  min −1 among girls were cut‐points to identify those at increased cardiometabolic risk. Appropriately controlling for body size and composition reduced the ability of cardiorespiratory fitness to identify children at increased cardiometabolic risk.